Finite-control-set model predictive control for magnetically coupled wireless power transfer systems - Qi, Chen; Lang, Zhengying; Li, Tao; Chen, Xiyou (JOURNAL OF POWER ELECTRONICS, 2021)
Output voltage control is an important subject in magnetically coupled wireless power transfer (MC-WPT) applications. Conventional control methods for MC-WPT systems use the PI controller. However, this method suffers from three issues: time-consuming tuning work of the PI parameters, increased control complexity due to the needs of the modulator, and poor dynamic performance. To provide an attractive alternative to the PI controller, a novel output voltage regulation method based on finite-control-set model predictive control (FCS-MPC) has been proposed for a MC-WPT system. The proposed method has inherent advantages such as a very intuitive concept, no need for a modulator, and fast dynamic response. Moreover, it can achieve soft switching by constructing pulse-density-modulation-based voltage pulse sequences as the control set. The design and implementation of the proposed controller are discussed in this paper. The proposed control method has been tested on a series-series-compensated MC-WPT system, and experimental results demonstrate the effectiveness of the proposed control method in comparison with PI control methods.